(untitled) (American Journal of Medical Science and Innovation, 2025)
The onset of anosmia, or temporary loss of smell, has emerged as a prominent neurological manifestation and an early indicator of COVID-19 infection. This retrospective study, conducted by the Dubai Health Authority (DHA) staff at the DHA COVID-19 Command & Control Center in Dubai – UAE, from May to July 2020, aimed to investigate the prevalence and characteristics of anosmia in COVID-19 patients. A total of 1075 patients were enrolled in the study, comprising 878 males (81.4%) and 201 females (18.6%). The median age ranged from 31 to 40 years. Patients with anosmia were compared to those without, with a particular focus on gender disparities and associated comorbidities, including diabetes, hypertension, heart disease, lung disease, and thyroid disease. The study found that 22% of COVID-19 patients presented with anosmia, the initial symptom in 47% of cases. Notably, 95% of patients experiencing anosmia recovered within two months. While there was no significant correlation between anosmia and comorbidities, such as diabetes, hypertension, heart disease, lung disease, and thyroid disease, there was also no association observed between anosmia and other common COVID-19 symptoms, such as fever, cough, shortness of breath, and diarrhoea. Anosmia, occurring in approximately 22% of COVID-19 cases, is a noteworthy early indicator of the infection. Despite its prevalence, anosmia has no significant correlation with comorbidities or other symptomatic manifestations of COVID-19, which underscores the importance of recognising anosmia as a distinct clinical feature in diagnosing and managing COVID-19.